KEBIJAKAN PROGRAM KREDIT USAHA RAKYAT (KUR) DENGAN SUKU BUNGA 9% DALAM PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DI KECAMATAN MEDAN AMPLAS - HANNA M Damanik; Melissa T. A Simarmata; Romindo M Pasaribu (JURNAL ILMIAH KOHESI, 2018)
The purpose of this study was to find out the implementation of the People's Business Credit Policy(KUR) with 9% interest intended for BRI-guided MSMEs in Amplas District.Another indicator of success is that the KUR program has succeeded in absorbing as much labor as possible20,344,639 people. Thus, the formulation of the problem in this study is How to ImplementPolicy for the People's Business Credit Program (KUR) with a 9% interest in MSME Development inAmplas District?The research subjects were residents of the Medan Amplas sub-district who were MSME actorswho are under the auspices of BRI and the management of BRI. The theory used in this studyis a theory put forward by Merilee S Grindle (2003), the contents of its policies include: (1)Interests affected by policy, (2) Types of benefits to be generated, (3) degreesdesired changes, (4) Position of policy makers, (5) Who is implementing the program, and (6)resources deployed. While the context of its implementation includes; (1) Power, Interest andStrategy of Actor Involved (power, interests and strategies of the actors involved), (2)Institution and Regine Characteristic (characteristics of the ruling institutions and regimes), (3) and Complianceand Responsiveness (level of compliance and the response from the implementer).The results of the study found that the distribution and from the KUR program were fully on target.This study found several cases regarding the funds from the KUR program which fell into the hands of the onesnot supposed to or not on productive efforts that have been determined byPrevious government. In this study there are several factors such as the inappropriate target andthe target of the KUR distribution target. The KUR program socialization activity is not only a role fromExecuting Bank, but it is the role of the regional government as an arm of theCentral government. Dissemination activities carried out by the regional government are good at the sub-district leveland related institutions can actually optimize the KUR program that the sedan is running.However, this is still not well implemented by the local government, namelythe government in the Medan Amplas district.The lack of roles from the regional government in implementing the KUR program can resultcustomers from KUR fund recipients especially for the actors in applying for loans without being noticedregional government.